A Learning Scenario on Figurative Language in Gita Savitri Devi's Novel Rentang Kisah - Mulkan Andika Situmorang; Izmawal Pebriani Nasution; Meliana Br Gultom; Mastari Ramadhani; Muji Endah Palupi (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The purpose of this study is to explain that a novel can be used as a learning scenario for figurative language that is easy to understand. This research employs a qualitative approach using descriptive methods. The data in this study is derived from a novel titled Rentang Kisah written by Gita Savitri Devi. The data source comes directly from the novel Rentang Kisah by Gita Savitri Devi. The results of this study indicate that a novel is not only meant to be enjoyed as a literary work but can also be developed into a learning scenario. By creating a learning scenario, it becomes easier to explain the figurative language found in Rentang Kisah by Gita Savitri Devi.